Two Cases of Abdominal Aortic Fenestration and Abdominal Aortic-Superior Mesenteric Artery Bypass for Stanford type B Acute Aortic Dissection with Intestinal Ischemia - Kamikubo, Yasuhiro; Sato, Koji; Ito, Masamichi; Takahira, Makoto (Japanese Journal of Vascular Surgery, 2012)
Critical organ perfusion abnormalities (malperfusion) are main causes of acute mortality and complications in acute aortic dissection. Entry closure in most cases of Stanford type A aortic dissection can provide reperfusion, while there is no established method in Stanford type B aortic dissection, thus we are required to perform individualized treatment. We present good results in 2 cases of abdominal aortic fenestration and bypass grafting between the aorta and superior mesenteric artery in type B acute aortic dissection with intestinal ischemia along with a review of the literature.